Effect of Gurney Flap Geometry on a S809 Airfoil - Li-Shu Hao; Yong-Wei Gao (International Journal of Aerospace Engineering)
In this paper, the effect of Gurney flap shapes on wind turbine blade airfoil S809 has been studied by numerical simulation. First, the O-type grid is used in the numerical simulation. By comparing with experimental data, such as the lift force, the drag coefficient, and the pressure distribution, the accuracy of the simulation method is validated. Second, the research on the widths of three kinds of rectangular Gurney flaps at the trailing edge of the S809 airfoil is carried out. Rectangular Gurney flaps can considerably increase the lift in both the linear and nonlinear sections, and the maximum lift coefficient can be increased by 20.65%. In addition, the drag and the pitching moment are increased. However, the width of the rectangular Gurney flap has a small impact on the lift, the drag, and the pitching moment. Finally, the effects of rectangular and triangular Gurney flaps on the aerodynamic characteristics of the S809 airfoil are compared. The results show that the triangular flaps can obtain an increase of maximum lift coefficient by 28.42%, which is better than 16.31% of the rectangular flaps.